Working Abroad in Ghana: Cultural Considerations in Radiologic Science - Botwe, B.O.; Antwi, W.K.; Arthur, L. (Radiologic Technology, 2018)
Many countries are experiencing a shortage of radiologic science professionals, prompting an increasing number of foreign technolo- gists to move to those countries. Some tech- nologists accept the challenge because they want to apply their skills where the need is greatest. Financial reasons entice others, whereas still others are drawn by the oppor- tunity to learn or experience something new. Whatever the individual motivation for this migration, the result is that a growing global need is being addressed.1 Working in a setting where the cultural aspects (eg, language, food, customs, traditions) are unfamiliar can be challenging. Culture shapes how people think and act, as well as how they interpret certain actions; it plays a role in every situation, including when patients receive medical care. Radiologic technologists who strive to learn about the people they serve experience fewer clashes and conf licts inherent in cross-cultural com- munication.2 In addition, adopting patient interaction practices that consider the prevailing cultural norms results in more patient cooperation and satisfaction dur- ing imaging examinations.